1986
DOI: 10.1007/bf00032122
|View full text |Cite
|
Sign up to set email alerts
|

Demography of Betula pubescens ssp. tortuosa sown in contrasting habitats close to the birch tree-limit in Central Sweden

Abstract: Seeds of mountain birch (Betula pubescens Ehrh. ssp. tortuosa (Ledeb.) Nyman) were sown on permanent plots in three contrasting habitats close to the birch tree-limit in Central Sweden. The habitats differed mainly in regard to the length of the growth period, as determined by the pattern of local snow-accumulation. Germination success, seedling demography (1981)(1982)(1983) and related aspects of the early stages were studied. Germination was found to start shortly after snowmelt in the year after ripening, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…We found extremely low values of seedling survival after the first summer. This was a common characteristic of our four populations and also of all previous studies on birches across Europe (Kinnaird 1974;Miles and Kinnaird 1979;Kullman 1986;Skoglund and Verwijst 1989;Laskurain et al 2003). These studies also found frost damage during the first winter to be the second cause of seedling mortality.…”
Section: Seed Dispersal: the Unlikely Colonisation Of Empty Habitat Pmentioning
confidence: 58%
See 2 more Smart Citations
“…We found extremely low values of seedling survival after the first summer. This was a common characteristic of our four populations and also of all previous studies on birches across Europe (Kinnaird 1974;Miles and Kinnaird 1979;Kullman 1986;Skoglund and Verwijst 1989;Laskurain et al 2003). These studies also found frost damage during the first winter to be the second cause of seedling mortality.…”
Section: Seed Dispersal: the Unlikely Colonisation Of Empty Habitat Pmentioning
confidence: 58%
“…The limiting role played by germination in birch population recruitment has been discussed by Kullman (1986), who suggested that seed germination was not an important bottleneck in the life cycle of mountain birch (Betula pubescens subsp. tortuosa) because a large seed The circles indicate the "spatial range" of the seed-density patterns, i.e.…”
Section: Seed Production and Viability: Magnitude And Variation Amongmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the birch decline at 8200 cal.years (7500 14 C years) BP was probably not caused by increasing aridity (cf. [Kullman 1986]; [MacDonald 1993]). The initial deforestation is simultaneous with a pronounced cooling (8200-event) recorded in Greenland ice cores ( [Johnsen 1992]) and which seems to have had global impact ( [Dahl and Nesje 1996]; [Alley 1997]; [Stager and Mayewski 1997]; [Haas 1998]).…”
Section: The Holocenementioning
confidence: 99%
“…In the U.S. Rocky Mountains, Abies lasciocarpa and Picea engelmannii have been linked to shadow effects of tree clumps (Butler et al 2004, Hättenschwiler and Smith 1999, Maher et al 2005, Daly and Shankman 1985. Shading the ground by the canopy reduces winter/spring sun radiation and night time radiation, reducing the risk of winter desiccation (Kullman 2007 (Hughes et al 2009, Kullman 1985, Autio and Colpaert 2005, Kullman and Öberg 2009respectively). In the Pacific Northwest (PNW), Abies lasciocarpa and Tsuga meriensiana have been associated with ridges and convexities (Brink 1959, Lowery 1972, Rochefort and Peterson 1996 (Gratzer 1999, Ziolonka and Niklossen 2004, Motta et al 2006, Baier et al 2007, Ran et al 2010.…”
Section: Introductionmentioning
confidence: 99%